2015
DOI: 10.1038/srep13633
|View full text |Cite
|
Sign up to set email alerts
|

Memory reconsolidation may be disrupted by a distractor stimulus presented during reactivation

Abstract: Memories can be destabilized by the reexposure to the training context, and may reconsolidate into a modified engram. Reconsolidation relies on some particular molecular mechanisms involving LVGCCs and GluN2B-containing NMDARs. In this study we investigate the interference caused by the presence of a distractor - a brief, unanticipated stimulus that impair a fear memory expression - during the reactivation session, and tested the hypothesis that this disruptive effect relies on a reconsolidation process. Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…A GluN2B-induced memory destabilization was also later described by Crestani et al (2015) and Ferrer Monti et al (2016). Both used a distractor stimulus to erase memory in a memory retrieval-dependent matter.…”
Section: Camkii Memory Destabilization and Glun2bsupporting
confidence: 55%
See 3 more Smart Citations
“…A GluN2B-induced memory destabilization was also later described by Crestani et al (2015) and Ferrer Monti et al (2016). Both used a distractor stimulus to erase memory in a memory retrieval-dependent matter.…”
Section: Camkii Memory Destabilization and Glun2bsupporting
confidence: 55%
“…Aside from the involvement of Ca 2+ influx, which is mediated by L‐type voltage‐gated calcium channels (Crestani et al . ), not much is known about the mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies showed that the reconsolidation of a fearful memory could be disrupted after its reactivation followed by a distractor stimuli (air puff) or the exploration of a hole board (Boccia et al, 2005; Crestani et al, 2015). In humans, for example, Schwabe and Wolf (2009) showed that learning a neutral story after reactivation of different autobiographical memories (positive, negative, or neutral), reduced specifically the retention of neutral memories.…”
Section: Discussionmentioning
confidence: 99%